Pediatric laryngotracheal separation following a go-cart injury. (June 2016) - Jitpakdee, Polpatt; Steele, Toby; Bhuskute, Aditi; Setabutr, Dhave
Abstract: Less than one percent of trauma admission cases are categorized as pediatric neck trauma[13] . Nevertheless, due to an increasingly mobile society, there has been an increasing frequency of pediatric neck trauma with motor vehicle accidents being the most common mechanism of injury[8] . We present a case of laryngotracheal separation from a blunt, clothesline injury to the neck in a pediatric patient. We also review the literature and discuss the benefit of balloon airway dilation and its assistance in the management of laryngeal trauma and its resultant effects.